An investigation into aflatoxin M1 in slaughtered fattening pigs and awareness of aflatoxins in Vietnam - Hu Suk Lee; Lindahl, Johanna F.; Hung Nguyen-Viet; Nguyen Viet Khong; Vuong Bui Nghia; Huyen Nguyen Xuan; Grace, Delia (Springer, 2017)
Background Aflatoxin M1 (AFM1) is a hydroxylated metabolite formed after aflatoxin B1 (AFB1) is consumed by humans and animals; it can be detected in urine, milk and blood. It is well recognized that AFB1 is toxic to humans and other animals. The International Agency for Research on Cancer (IARC) classifies aflatoxins as group 1 carcinogens and AFM1 as group 2B carcinogen. The main objective of this study was to evaluate the exposure of pigs to aflatoxins as well as to assess the public awareness of aflatoxins among people in five provinces in Vietnam. Results A total of 1920 urine samples were collected from slaughterhouses located in five provinces. Overall, the positive rate of AFM1 was 53.90% (95% confidence interval 51.64–56.15) using a cut-off of 0.15 μg/kg (range: limit of detection to 13.66 μg/kg, median: 0.2 μg/kg and mean: 0.63 μg/kg). A total of 252 people from the general population were interviewed from 5 provinces, and overall 67.86% reported being aware of aflatoxins. We also found that men and more highly educated had significantly increased awareness of aflatoxins compared to the females and primary/secondary school group. The respective odds ratios (ORs) were as follows: “male” group (OR: 2.64), “high school educated” group (OR: 3.40) and “college/university or more educated” group (OR: 10.20). Conclusions We can conclude that pigs in Vietnam are exposed to aflatoxins to varying degrees, and there may be a risk that pork products could contain AFM1. Further investigation is needed into the possible health impacts as well as to aid in establishing regulations for animal feed to reduce the health impacts in humans and animals.